The Prognostic Value of Serum HBV-RNA during Hepatitis B Virus Infection is Related to Acute-on-Chronic Liver Failure - Keli Qian; Ying Xue; Hang Sun; Ting Lu; Yixuan Wang; Xiaofeng Shi (Canadian Journal of Gastroenterology and Hepatology)
Background. Serum HBV-RNA levels can predict antiviral response in chronic hepatitis B (CHB) patients; however, its role in HBV-related ACLF (HBV-ACLF) remains unclear. Here, we determined its implications for HBV-ACLF. Methods. Baseline serum HBV-RNA levels were retrospectively detected in HBV-ACLF and CHB patients. The association of serum HBV-RNA level with clinical outcomes was evaluated by performing multiple logistic regression. A nomogram was developed to formulate an algorithm incorporating serum HBV-RNA for predicting the survival of HBV-ACLF patients. After being discharged from the hospital, the HBV-ACLF patients were followed up for 36 weeks. Results. In this study, 82 HBV-ACLF patients and 33 CHB patients were included. Serum HBV-RNA levels were significantly higher in CHB patients than in HBV-ACLF patients (4.15 ± 2.63 log10 copies/mL VS 5.37 ± 2.02 log10 copies/mL) (P<0.05). Among the HBV-ACLF cases, patients with poor outcomes had lower serum HBV-RNA levels, but the difference was not significant. The area under the receiver operating characteristic curve of the serum HBV-RNA inclusive model was 0.745, superior to 0.66 from MELD scores (P<0.05). During the follow-up for four weeks, the serum HBV-RNA levels, especially in the survival group, were found to be lower than the baseline levels. Conclusions. Serum HBV-RNA levels were associated with disease severity and might predict the long-term clinical outcome of HBV-ACLF patients.